Purwarupa Spirometer Digital Berbasis LABVIEW - Wahyu Sabani; Budi Sumanto (Jurnal Listrik, Instrumentasi, dan Elektronika Terapan, 2021)
Spirometer is an instrument used to measure the vital capacity of the human lung and is usually only found in large hospitals or clinical laboratories because of its relatively high price. However, to find out how this instrument works, a prototype of the spirometer is made by utilizing a Labview-based interface. This prototype was developed by making an air channel or funnel the size of a human mouth which then the air will be detected by a pressure sensor connected to a signal conditioning circuit and then the measurement information data is forwarded by the Arduino to a computer to be processed into digital data which is then converted into vital capacity information data. lungs. The results obtained from this research are that it can make a spirometer prototype according to its function which is hoped to be used as a learning medium in the field of medical instrumentation by measuring the vital capacity of the lungs in the form of height, age, and gender of a person, besides that the results are in the form of a graphic display. and numerical data from the measurement process on the GUI display in LabVIEW. This prototype was calibrated using a syringe with a volume of 2 liters and the accuracy rate was 99.63% with a standard deviation value of ± 70.61 ml and a precision value of 1.76% from these results.